Women online: A study of Common Service Centres in India using a capability approach. Issue 3 (20th October 2022) - Rajeev, Meenakshi; Bhandarkar, Supriya
Abstract: Income‐generating activities by women are an effective means of reducing gender‐based deprivation and disparities. In the constrained familial and community settings of developing economies, online platforms can be an appropriate means for women to carry out economic activities. In this context, important initiatives taken by the Government of India, such as the Common Service Centres scheme, are worth studying. This paper critically evaluates such revolutionary online platform–based entrepreneurial initiatives using the capability approach developed by Amartya Sen. We examine through case studies how women‐run businesses use online platforms and what determines their success, inputs, capabilities, and conversion factors. Further, national enterprise‐level data from Indiaʼs National Sample Survey Office are analysed to show that states with a higher level of gender inequality are also the regions with a lower level of information and communications technology usage by women‐run enterprises.